2022
DOI: 10.1186/s40814-022-01205-x
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness training for community-based psychotherapists: a feasibility study

Abstract: Background While mindfulness training’s feasibility has been assessed in many health care settings, the feasibility of teaching mindfulness to psychotherapists of various orientations for both self- and patient-care has not been explored. The objectives of this feasibility assessment were to determine the degree to which clinic psychotherapists were willing to complete a skills-based mindfulness training program; evaluate the acceptability of integrating mindfulness interventions into an urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
2
2
0
Order By: Relevance
“…The study showed a high increment in awareness level, access, willingness to purchase and use of LLINs. The association between community involvement and malaria awareness is consistent with other malaria studies conducted in Rwanda and Malawi which found that community involvement in malaria control intervention increased awareness of malaria and the intervention being implemented [22,23].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The study showed a high increment in awareness level, access, willingness to purchase and use of LLINs. The association between community involvement and malaria awareness is consistent with other malaria studies conducted in Rwanda and Malawi which found that community involvement in malaria control intervention increased awareness of malaria and the intervention being implemented [22,23].…”
Section: Discussionsupporting
confidence: 88%
“…The study showed a high increment in awareness level, access, willingness to purchase and use of LLINs. The association between community involvement and malaria awareness is consistent with other malaria studies conducted in Rwanda and Malawi which found that community involvement in malaria control intervention increased awareness of malaria and the intervention being implemented [ 22 , 23 ]. A high awareness level among community members could also help address community misconceptions about LLIN use as becoming knowledgeable about malaria prevention strategies will consequently increase LLIN use among community members [ 6 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This suggests that the CHAT intervention is a good fit with the value system of the community members and is regarded as practical and adequate for further implementation. Studies have shown that high appropriateness and feasibility are necessary requirements for successful intervention implementation and the achievement of intervention outcomes [18][19][20].…”
Section: Discussionmentioning
confidence: 99%